Short communication: Acute but transient increase in serum insulin reduces messenger RNA expression of hepatic enzymes associated with progesterone catabolism in dairy cows - Vieira, F. V R [UNESP]; Cooke, Reinaldo Fernandes [UNESP]; Aboin, A. C. [UNESP]; Lima, P. [UNESP]; Vasconcelos, José Luiz Moraes [UNESP] (American Dairy Science Association, 2013)
The objective of this experiment was to evaluate the effects of glucose infusion on serum concentrations of glucose, insulin, and progesterone (P4), as well as mRNA expression of hepatic CYP2C19 and CYP3A4 in nonlactating, ovariectomized cows in adequate nutritional status. Eight Gir × Holstein cows were maintained on a low-quality Brachiaria brizantha pasture with reduced forage availability, but they individually received, on average, 3. kg/cow daily (as fed) of a corn-based concentrate from d -28 to 0 of the experiment. All cows had an intravaginal P4-releasing device inserted on d -14, which remained in cows until the end of the experiment (d 1). On d 0, cows were randomly assigned to receive, in a crossover design containing 2 periods of 24. h each (d 0 and 1), (1) an intravenous glucose infusion (GLUC; 0.5. g of glucose/kg of BW, over a 3-h period) or (2) an intravenous saline infusion (SAL; 0.9%, over a 3-h period). Cows were fasted for 12. h before infusions, and they remained fasted during infusion and sample collections. Blood samples were collected at 0, 3, and 6. h relative to the beginning of infusions. Liver biopsies were performed concurrently with blood collections at 0 and 3. h. After the last blood collection of period 1, cows received concentrate and returned to pasture. Cows gained BW (16.5 ± 3.6. kg) and BCS (0.08 ± 0.06) from d -28 to 0. Cows receiving GLUC had greater serum glucose and insulin concentrations at 3. h compared with SAL cohorts. No treatment effects were detected for serum P4 concentrations, although mRNA expression of CYP2C19 and CYP3A4 after the infusion period was reduced for cows in the GLUC treatment compared with their cohorts in the SAL treatment. In conclusion, hepatic CYP3A4 and CYP2C19 mRNA expression can be promptly modulated by glucose infusion followed by acute increases in circulating insulin, which provides novel insight into the physiological mechanisms associating nutrition and reproductive function in dairy cows. © 2013 American Dairy Science Association.
Keywords: Dairy cow; Glucose infusion; Hepatic enzyme; Progesterone; cytochrome P450 3A; glucose; insulin; messenger RNA; progesterone; unspecific monooxygenase; animal; biosynthesis; blood; cattle; enzymology; female; liver; metabolism; physiology; Animals; Aryl Hydrocarbon Hydroxylases; Cattle; Cytochrome P-450 CYP3A; Female; Glucose; Insulin; Liver; Metabolism; RNA, Messenger; Bos; Brachiaria; Urochloa brizantha; Zea mays